NON-BIOLOGICAL COMPLEX DRUGS CONCEPT IN GENERIC DRUGS DEVELOPMENT - D. V. Goryachev; Yu. V. Chernova; N. E. Uvarova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Expansion of the range of new medicines leads to a significant increase in healthcare spending and, consequently, to the appearance of more affordable generic drugs. A drug can be recognised as generic if there is sufficient evidence of equivalent structural characteristics of the active substance and therapeutic characteristics of the drug. However, for a number of substances which are multicomponent mixtures of sister compounds it is quite difficult to demonstrate absolute similarity of the chemical structure and to determine a substrate for bioavailability evaluation. Therefore, a separate group of non-biological complex drugs has been singled out. The present article summarises the requirements of the leading regulatory agencies for demonstration of equivalence between the reference product and such medicines as glatiramoids, liposome-encapsulated doxorubicin and iron-based nanosized colloidal products. It has been shown that preclinical and clinical studies are still necessary for these types of products, and the amount of testing will depend on the results of comparability assessment.